More Than Migrants: Navigating Intra-Group Social Belonging and Identity Among South Asians in the UAE - Qureshi, Zainab (2025)
A Master of Arts in International Studies by Zainab Qureshi entitled, “More Than Migrants: Navigating Intra-Group Social Belonging and Identity Among South Asians in the UAE”, submitted in December 2025. Thesis advisor is Dr. Neha Vora. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).